2012
DOI: 10.1530/rep-11-0215
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures to define spermatogenic cells in common marmoset (Callithrix jacchus)

Abstract: Germ cell development is a fundamental process required to produce offspring. The developmental program of spermatogenesis has been assumed to be similar among mammals. However, recent studies have revealed differences in the molecular properties of primate germ cells compared with the well-characterized mouse germ cells. This may prevent simple application of rodent insights into higher primates. Therefore, thorough investigation of primate germ cells is necessary, as this may lead to the development of more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Moreover, the marmoset monkey was the first transgenic non-human primate with germ line transmission ( Sasaki et al , 2009 ). However, in sharp contrast to the relatively well-characterized post-natal testicular germ cell development ( Chandolia et al , 2006 ; Mitchell et al , 2008 ; McKinnell et al , 2009 ; Aeckerle et al , 2012 ; Eildermann et al , 2012 ; Lin et al , 2012 ), embryonic germ cell development is poorly understood, or even uninvestigated, in the marmoset monkey ( Li et al , 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the marmoset monkey was the first transgenic non-human primate with germ line transmission ( Sasaki et al , 2009 ). However, in sharp contrast to the relatively well-characterized post-natal testicular germ cell development ( Chandolia et al , 2006 ; Mitchell et al , 2008 ; McKinnell et al , 2009 ; Aeckerle et al , 2012 ; Eildermann et al , 2012 ; Lin et al , 2012 ), embryonic germ cell development is poorly understood, or even uninvestigated, in the marmoset monkey ( Li et al , 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study showed that spermatogenesis defects, such as idiopathic azoospermia or severe oligospermia, were also associated with a hypermethylated Vasa promoter in some individuals [48]. Lin et al [49] reported that some germ cell-specific genes (e.g. Nanog, Pou5f1, and Zp1) in the marmoset and mouse testis showed different expression patterns and methylation patterns, but the expression patterns and methylation patterns of Vasa and some imprinted genes are conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the methylation status of Oct-3/4 promoter was performed by the bisulfite conversion method as described previously [ 21 ]. In brief, bisulfite treatment of genomic DNA converts unmethylated cytosines into uracil; respective changes were detected by PCR amplification followed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%